2008
DOI: 10.4315/0362-028x-71.9.1774
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Virulence-Associated Genes in Escherichia coli O157 and Non-O157 Isolates from Beef Cattle, Humans, and Chickens

Abstract: Food-producing animals can be reservoirs of pathogenic Escherichia coli strains that can induce diseases in animals or humans. Contamination of food by E. coli O157:H7 raises immediate concerns about public health, although it is not clear whether all E. coli O157 isolates of animal origin are equally harmful to humans. Inversely, the pathogenic potential of atypical E. coli O157 isolates and several non-O157 serotypes often is ignored. We used a DNA microarray capable of detecting a subset of 346 genes to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Differences between those lineages were recently highlighted by us and others (Maldonado et al, 2005;Dowd and Ishizaki, 2006;Rashid et al, 2006;Besser et al, 2007;Lefebvre et al, 2008). Indeed, using DNA hybridization on arrays, we previously showed that O157:H7 isolates from beef cattle were genetically different from human isolates but possessed a similar virulence potential or, more precisely, a similar set of virulence genes (Lefebvre et al, 2008).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Differences between those lineages were recently highlighted by us and others (Maldonado et al, 2005;Dowd and Ishizaki, 2006;Rashid et al, 2006;Besser et al, 2007;Lefebvre et al, 2008). Indeed, using DNA hybridization on arrays, we previously showed that O157:H7 isolates from beef cattle were genetically different from human isolates but possessed a similar virulence potential or, more precisely, a similar set of virulence genes (Lefebvre et al, 2008).…”
Section: Introductionmentioning
confidence: 83%
“…Bovine isolates are identified by a number in parentheses, followed by a typing code (1-12), a pen number (1-16), and the sampling day (4-165) of the longitudinal study described before (Lefebvre et al, 2005). Isolates identified by a black dot were also previously compared by microarray analysis (Lefebvre et al, 2008). often different based on the presence or absence of some genomic regions and Stx-encoding bacteriophage insertion sites (Besser et al, 2007;Steele et al, 2007;Zhang et al, 2007). In a previous study, we also confirmed that O157:H7 isolates from beef cattle and human clinical cases clustered distinctly, supporting thus the existence of at least two different lineages of O157:H7 (Lefebvre et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology which provided the key step change in enabling highly multiplexed molecular analysis is DNA microarrays. It has been used for bacterial and viral typing since their early days and systems for microbial species typing [3,4], antibiotic resistance detection [5][6][7][8] and virulence assessment [9,10] have been described. For a review closest to the field see [11] and [12].…”
Section: Biophotonicsmentioning
confidence: 99%
“…Further promising technologies employ protein binders, peptides, aptamers, etc. as recognition elements often in an arrayed format to increase the multiplexing capability [10,15,16]. Diagnostics of infectious diseases can be also approached from the host response to infection by measurement of nucleic acid [17,18] and metabolomic biomarkers [19].…”
Section: Biophotonicsmentioning
confidence: 99%